A multi-strain probiotic blend reshaped obesity-related gut dysbiosis and improved lipid metabolism in obese children - Chen, An-Chyi; Fang, Tzu-Jung; Ho, Hsieh-Hsun; Chen, Jui-Fen; Kuo, Yi-Wei; Huang, Yen-Yu; Tsai, Shin-Yu; Wu, Shu-Fen; Lin, Hung-Chih; Yeh, Yao-Tsung (Frontiers in Nutrition, 2022)
Abstract Background and Aims: Obese children are more prone to becoming obese adults, and excess adiposity consequently increases the risk of many complications, such as metabolic syndromes, nonalcoholic fatty liver disease, cardiovascular disease, etc. This study aimed to evaluate the effects of multi-strain probiotics on the gut microbiota and weight control in obese children. Methods: A double-blind, randomized, placebo-controlled trial was carried out in overweight and obese children. Subjects received 12 weeks of treatment with supplementary probiotics that contained three strains: Lactobacillus salivarius AP-32, Lactobacillus rhamnosus bv-77, and Bifidobacterium animalis CP-9, plus diet and exercise guidance. A total of 82 children were enrolled, and 53 children completed the study. Results: The supplementation of multi-strain probiotics resulted in a significant effect demonstrating HDL and adiponectin elevation. At the same time, BMI and serum total cholesterol, LDL, leptin, and TNF-α levels were reduced. Lactobacillus spp. and Bifidobacterium animalis were particularly increased in subjects who received probiotic supplements. The abundance of Lactobacillus spp. was inversely correlated with the ether lipid metabolism pathway, while that of B. animalis was positively correlated with serum adiponectin levels. Conclusion: Our results show that obesity-related gut dysbiosis can be reshaped by the supplementation of a multi-strain probiotic to improve lipid metabolism. The regular administration of a multi-strain probiotic supplement may be helpful for weight control and health management in overweight and obese children